Marketing Strategy Analysis of Zoe Dessert Café in Pantai Indah Kapuk North Jakarta - Gustian Yulius, Kevin; Wu, Tiffany (Jurnal Sains dan Teknologi, 2024)
This study examines the marketing strategy of Zoé Dessert Café in Pantai Indah Kapuk, North Jakarta, within the context of Indonesia's rapidly growing culinary industry. The objective is to assess the café's market potential, competitive landscape, and strategic positioning. A quantitative survey method was employed, collecting data from residents of North Jakarta through questionnaires. The analysis focused on market potential, trends, competitor evaluation, SWOT analysis, and the marketing mix. Results indicate a strong market potential among the 20-44 age group, with a notable interest in unique dessert experiences. Competitor analysis revealed the presence of direct and indirect competitors, emphasizing the need for Zoé Dessert Café to adopt innovative strategies. The SWOT analysis identified strengths such as the café's unique animal-themed desserts and strategic location, while addressing challenges like limited menu variety and brand recognition. Recommended strategies include leveraging social media for promotions, maintaining high-quality standards, fostering customer relationships, and continuous innovation. The segmentation, targeting, and positioning (STP) strategy focuses on young adults and professionals in North Jakarta who frequent cafés and enjoy desserts. The marketing mix strategy highlights diverse products, competitive pricing, strategic location, robust promotional activities, exceptional service quality, appealing packaging, engaging programs, and strategic partnerships.